ANTITUMOR EFFECT OF DECALEPIS HAMILTONII ROOT EXTRACT AGAINST EHRLICH ASCITES TUMOR IN MICE - MAHSA ZAREI; T. SHIVANANDAPPA (International Journal of Pharma and Bio Sciences, 2013)
The antitumor activity of Decalepis hamiltonii root extract (DHA) was investigated in Ehrlich Ascites Tumor (EAT) cell model in mice and the effect was compared with that of the anticancer drug, cyclophosphamide (CP). Treatment of EAT cell bearing mice with aqueous extract of Decalepis hamiltonii (50 mg/kg and 100 mg/kg b.w.) showed a significant reduction in ascites tumor volume, tumor cell counts and increased median survival time (MST). EAT cells induced alterations in hematological profile and the serum marker enzymes aspartate and alanine transaminases (AST, ALT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) were restored by DHA treatment. The antitumor effect of DHA was comparable to that of the anticancer drug cyclophosphamide suggesting the anticancer potential of the root extract of Decalepis hamiltonii.